Synthesis and applications of nanocarbons - Arnault, Jean-Charles, 1966-; Eder, Dominik (Nanocarbon chemistry and interfaces., 2021)
"This book will discuss the synthesis, properties, characterization and applications of various different nanocarbons including nanodiamonds, nanotubes, graphene, fullerenes, and carbon dots. It will also introduce new types of nanocarbon hybrids, promising next-generation functional materials for environmental and sustainable energy applications, for example nanodiamond-metal, nanodiamond-inorganic and nanodiamond-graphene hybrids. The book provides a transversal view of assets and applications of the different carbon nanomaterials and their hybrids, helping to share knowledge between each community of carbon materials"--